2020
DOI: 10.1136/bmj.m1443
|View full text |Cite
|
Sign up to set email alerts
|

Viral load dynamics and disease severity in patients infected with SARS-CoV-2 in Zhejiang province, China, January-March 2020: retrospective cohort study

Abstract: Objective To evaluate viral loads at different stages of disease progression in patients infected with the 2019 severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) during the first four months of the epidemic in Zhejiang province, China. Design Retrospective cohort study. setting A designated hospital for patients with covid-19 in Zhejiang province, China. ParticiPants 96 consecutively admitted patients with laboratory confirmed SARS-CoV-2 infection: 22 with mild disease and 74 with severe disease. Da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

112
1,548
11
43

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,401 publications
(1,714 citation statements)
references
References 32 publications
112
1,548
11
43
Order By: Relevance
“…3 In one study, PCR positivity in stool was observed in 55 of 96 (57%) infected patients and remained positive in stool beyond nasopharyngeal swab by a median of 4 to 11 days, but was unrelated to clinical severity. 2 Persistence of PCR in sputum and stool was found to be similar as assessed by Wölfel et al 3 In a study of 205 patients with confirmed COVID-19 infection, RT-PCR positivity was highest in bronchoalveolar lavage specimens (93%), followed by sputum (72%), nasal swab (63%), and pharyngeal swab (32%). 5 False-negative results mainly occurred due to inappropriate timing of sample collection in relation to illness onset and deficiency in sampling technique, especially of nasopharyngeal swabs.…”
supporting
confidence: 65%
“…3 In one study, PCR positivity in stool was observed in 55 of 96 (57%) infected patients and remained positive in stool beyond nasopharyngeal swab by a median of 4 to 11 days, but was unrelated to clinical severity. 2 Persistence of PCR in sputum and stool was found to be similar as assessed by Wölfel et al 3 In a study of 205 patients with confirmed COVID-19 infection, RT-PCR positivity was highest in bronchoalveolar lavage specimens (93%), followed by sputum (72%), nasal swab (63%), and pharyngeal swab (32%). 5 False-negative results mainly occurred due to inappropriate timing of sample collection in relation to illness onset and deficiency in sampling technique, especially of nasopharyngeal swabs.…”
supporting
confidence: 65%
“…Viral load dynamics and disease severity were reported by Zheng et al [14]. From 96 consecutive patients, RNA viral load was measured in respiratory, stool, serum and urine samples (total number of samples 3497).…”
Section: Viremia and Viral Loadmentioning
confidence: 94%
“…severity of SARS-CoV-2 infection (Zheng et al, 2020). The time to reach a detectable viral load depends on the growth rate of the viral population, which is to the leading order…”
Section: Time To Detectable Viral Loadmentioning
confidence: 99%